Quality of life in parents of autistic children: A transcultural perspective - Eapen, Valsamma; Karlov, Lisa; John, James Rufus; Beneytez, Carmen; Grimes, Poppy Z.; Kang, Ying Qi; Mardare, Ileana; Minca, Dana Galieta; Voicu, Laura; Malek, Khasnur Abd; Ramkumar, Aishworiya; Stefanik, Krisztina; et al. (Frontiers in Psychology, 2023)
Introduction: The concepts of health, illness, and disability as well as the perceptions of autism and quality of life (QoL) vary greatly across cultures and across time. This study sought to explore the interplay of culture on QoL and impact on parents caring for autistic children. Methods: We used a transcultural dataset from seven countries (Australia, Hungary, Malaysia, Romania, Singapore, Spain, and the United Kingdom) with participating parents/carers reporting on the Quality of Life in Autism (QoLA) questionnaire. The QoLA questionnaire is a validated measure of QoL for parents of autistic children, with Part A subscale measuring parental QoL and part B subscale assessing the parental impact of the child’s autism spectrum disorder (ASD) symptoms or features. We used the Quade's ranked analysis of covariance to determine significant differences between the countries in relation to QoLA Part A and Part B scores whilst adjusting for baseline differences using covariates such as parents’ gender, child’s age, and gender. Additionally, a post-hoc analysis with Bonferroni correction was also conducted to examine multiple pairwise comparisons. Results and conclusion: We found that while the effect of features of ASD (Part B subscale) stayed strongly comparable between cultures, the self-reported parental QoL was most likely determined by different aspects of culture in different countries. It is concluded that whilst the ASD symptoms or features appear to affect parents in the same way across different countries, the parental QoL may be a culturally informed construct.